Structural violence and everyday survival during COVID-19 lockdown: the experiences of street children in Uyo, Nigeria - Onayemi, Olayinka M. (International journal of law, crime and justice, 2024)
Background Most studies on the effect of covid-19 lockdowns on children have focused on those in regular family settings and in-school children. Research on the experiences of street children during lockdown are scarce. Our study seeks to fill this gap by exploring the negative effects of lockdowns on street children in a commercial city in South-South Nigeria, and how they coped with these effects. Method Using purposive sampling technique, we recruited twenty-four street children for the semi-structured interviews. Thematic analysis was used in identifying specific themes on the effect of COVID-19 lockdown on street children. Results All children interviewed reported direct adverse socioeconomic effects of COVID-19 lockdown. Also, they reported being victimised by law enforcement agents and adult street actors. Their public perception as a ‘diseased category’ capable of COVID-19 transmission contributed to stigma and eviction from places of abode, a situation that exposed some female street children to sexual violence. Street children coped with economic effects of lockdown through exploring further opportunities for income generation. Conclusion Street children bear a disproportionate effect of COVID-19 lockdown. There exists a need to prioritize their needs as well as include them in social protection measures for COVID-19.